Animal allergens: Common protein characteristics featuring their allergenicity - Christiane Hilger (Frontiers Research Topics, 2015)
Among the many molecules present in our environment, some have the property to induce allergic sensitization and IgE-mediated reactions. The analysis of known major animal allergens has shown that most belong to single protein families: lipocalins and serum albumins for inhalant allergens, EF-hand proteins, tropomyosins and caseins for the digestive allergens. The finding that allergens are often clustered in large families may be related to the fact that common structural, biochemical or functional features contribute to their allergenicity, in addition to external adjuvant factors. Currently, there is no curative treatment for animal allergy available. In order to lower allergic reactions to respiratory allergens in daily life and to food allergens upon accidental exposure, it is important to desensitize concerned patients. Tolerance induction by allergen-specific immunotherapy is in the current focus of an ambitious research. This Research Topic aims to provide a comprehensive view of the basic and recent insights on the allergenicity of animal allergens in view of their structural and functional aspects as well as allergen-specific immunotherapy.